Two new species of Clidicus Laporte, 1832 (Coleoptera: Staphylinidae: Scydmaeninae) from Yunnan, China - Cheng, Zhi-Fei; Yin, Zi-Wei (Zootaxa, 2019)
The Australo-Oriental genus Clidicus Laporte, 1832 is represented in China by a single species. Here we describe two new species from Yunnan: C. qiuae sp. nov. and C. yingjiangus sp. nov., which represent the northernmost records of the genus. A key to the Chinese species, and a world distributional map of Clidicus are provided.